Diversity and Potential of Herb Vegetation in Forest Area With Special Purpose (KHDTK) Kaliurang Yogyakarta as Medicines - Yuskianti, Vivi Yuskianti; Miladiyah, Miladiyah Hutami Saadi; Handayani, Trikinasih Handayani (Jurnal Wasian, 2019)
Information on the diversity of plants, especially herbs and their potential as medicines is not widely known. This study aims to determine the diversity of herbs and their potential as medicines in the research forest area of Mount Merapi, KHDTK Kaliurang, Yogyakarta. The study in three areas found 27 species herbs with Centhoteca lappacea (L) Desv had the highest average Important Value Index (79.26 %) and Fimbristylis dichotoma (L.) Vahl as the lowest (2.66 %). The Diversity Index (H’) of herbs in KHDTK Kaliurang is low (0.58-0.78). Its use and potential as medicines are found in 21 out of 27 herbs species. These herbs have been widely used for traditional medicine in many countries and further research also show the potential of these herbs for various diseases such as treatment of wounds, urinary problem, fever, diarrhea, anti-oxidant, diabetes, and cancer. Results of this study are expected to provide information on the potential of herbs for traditional and modern medicine. Furthermore, information on the diversity of these herbs can also complement the type of plants in the Mount Merapi region and increasing awareness on the importance of supporting efffort to utilize and preserve the herbs of the Merapi Mountain region, especially in the KHDTK Kaliurang.